Detection of cracks in building facades using infrared thermography - Fonseca, T.; Ferreira, J. (Innovations in bio-inspired computing and applications: Proceedings of the 13th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2022), 2023)
Cracks in building facades can deteriorate the health of a building, putting in risk the well being of the people who use it or that are in its surroundings. Identifying the cracks and assessing the damage degree of a facade is essential to the maintenance life cycle of a building. Infrared thermography has been playing a major role in identifying cracks and other defects in building facades. The aim of this paper is to develop a simple quantitative model to assess the damage degree of the facades of two public schools managed by Lisbon city council using infrared thermography. It is observed that the measurement of Thermal Contrast profiles of the facades produces effective results in identifying cracks in the facades.